Role of pattern recognition receptors and interferon-beta in protecting bat cell lines from encephalomyocarditis virus and Japanese encephalitis virus infection - Tarigan, Ronald; Shimoda, Hiroshi; Doysabas, Karla Cristine C.; Ken, Maeda; Iida, Atsuo; Hondo, Eiichi (Biochemical and biophysical research communications, 2020)
Bats are potential natural hosts of Encephalomyocarditis virus (EMCV) and Japanese encephalitis virus (JEV). Bats appear to have some unique features in their innate immune system that inhibit viral replication causing limited clinical symptoms, and thus, contributing to the virus spill over to humans. Here, kidney epithelial cell lines derived from four bat species (Pteropus dasymallus, Rousettus leschenaultii, Rhinolophus ferrumequinum, and Miniopterus fuliginosus) and two non-bat species (Homo sapiens and Mesocricetus auratus) were infected with EMCV and JEV. The replication of EMCV and JEV was lower in the bat cell lines derived from R. leschenaultii, R. ferrumequinum, and M. fuliginosus with a higher expression level of pattern recognition receptors (PRRs) (TLR3, RIG-I, and MDA5) and interferon-beta (IFN-β) than that in the non-bat cell lines and a bat cell line derived from P. dasymallus. The knockdown of TLR3, RIG-I, and MDA5 in Rhinolophus bat cell line using antisense RNA oligonucleotide led to decrease IFN-β expression and increased viral replication. These results suggest that TLR3, RIG-I, and MDA5 are important for antiviral response against EMCV and JEV in Rhinolophus bats. •Some bat cell lines showed a limited cytopathic effect after EMCV and JEV infection.•EMCV and JEV replication was inhibited in some bat cell lines.•Expression of PRRs and IFN-β was highly induced in some bat cell lines.•PRRs and IFN-β contributed to antiviral response against EMCV and JEV in bats.